Oral semaglutide improves body composition and preserves lean mass in patients with type 2 diabetes: a 26-week prospective real-life study - Volpe, Sara; Lisco, Giuseppe; Fanelli, Margherita; Racaniello, Davide; Colaianni, Valentina; Lavarra, Valentina; Triggiani, Domenico; Crudele, Lucilla; Triggiani, Vincenzo; Sabbà, Carlo; De Pergola, Giovanni; Piazzolla, Giuseppina (Frontiers in Endocrinology, 2023)
Background: Oral semaglutide is the first glucagon-like peptide-1 receptor agonist (GLP-1RA) designed for oral administration; it offers a promising opportunity to facilitate an early approach to Type 2 Diabetes (T2D). The study aimed to evaluate, in a real-life setting, the effects of oral semaglutide on the body composition of patients with T2D after 26 weeks of therapy. Methods: Thirty-two patients with T2D were evaluated at baseline (T0) and after three (T3) and six (T6) months of therapy with oral semaglutide. At each time point, body composition was assessed using a phase sensitive bioimpedance analyzer. Clinical, anthropometric and laboratory parameters, and the main biometric surrogates of liver steatosis and fibrosis, were also analyzed and compared. Results: A significant and early reduction in anthropometric and glucometabolic parameters, alanine aminotransferase, Fatty Liver Index, and Fat Mass was observed. Visceral Adipose Tissue (VAT) decreased, while Fat Free Mass and Skeletal Muscle Mass (SMM) increased during therapy, resulting in a beneficial increase in the SMM/VAT ratio. Finally, an overall improvement in body fluid distribution was observed. Conclusions: Our real-world data confirm the clinical efficacy of oral semaglutide and highlight its ability to improve the nutritional status of patients with T2D.